2007
DOI: 10.1007/s00213-007-0760-9
|View full text |Cite
|
Sign up to set email alerts
|

Experimental manipulation of attentional biases in heavy drinkers: do the effects generalise?

Abstract: The effects of attentional training show limited generalisation to different alcohol cues and methods of measuring cognitive bias. Experimentally increased attentional bias seems to increase subjective craving, but only among participants who are aware of the experimental contingencies that were in place during attentional training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
180
2
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(209 citation statements)
references
References 43 publications
23
180
2
4
Order By: Relevance
“…For example, Field and Eastwood (2005) showed that heavy social drinkers who were trained to direct their attention away from alcohol-related pictures showed a reduced attentional bias for such pictures. This result has been replicated a number of times (Field et al, 2007;Schoenmakers, Wiers, Jones, Bruce & Jansen, 2007;Schoenmakers et al, 2010).…”
Section: Biased Attentional Processing Of Food Cues and Modification mentioning
confidence: 76%
“…For example, Field and Eastwood (2005) showed that heavy social drinkers who were trained to direct their attention away from alcohol-related pictures showed a reduced attentional bias for such pictures. This result has been replicated a number of times (Field et al, 2007;Schoenmakers, Wiers, Jones, Bruce & Jansen, 2007;Schoenmakers et al, 2010).…”
Section: Biased Attentional Processing Of Food Cues and Modification mentioning
confidence: 76%
“…Early interventions to reduce bias in at risk adolescents or those with harmful levels of alcohol use could prevent attentional processing reaching automaticity and therefore reduce the impact of automatic orienting on alcohol use and craving. Training programmes implemented to reduce alcohol AB have had limited efficacy (Schoenmakers, Wiers, Jones, Bruce & Jansen, 2007;Field, Duka, Eastwood, Child, Santarcangelo & Gayton, 2007;Field & Eastwood, 2005). Such interventions may be more advantageous at earlier stages where AB is still under the influence of controlled attention and associations between alcohol use and alcohol cues can be extinguished before automaticity is reached.…”
Section: Presence Of Alcohol Attention Biasmentioning
confidence: 99%
“…The cause could be the specific content of our messages, or that BIs are unhelpful in changing alcohol consumption behaviour when delivered during drinking events. The latter explanation may be particularly relevant to heavy drinkers: previous research has shown that this population shows increased attentional biases that are thought to promote motivations for alcohol consumption and are resistant to manipulation [35][36][37][38]. Research that extends the parameters of our pilot study is needed to assess the effects of EMA and EMI on RSOD.…”
Section: Discussionmentioning
confidence: 94%